IMPLEMENTASI APLIKASI RPG MAKER VX ACE SEBAGAI SARANA GAME EDUKASI TIGA RAGAM BAHASA DI SMP NEGERI 2 PURBALINGGA - Nugroho, Lustiyono Prasetyo; Imron, Mohammad (STMIK KAPUTAMA, 2021)
School is a place for teaching and learning activities that are being carried out by each teacher to students, including theoretical and practical reviews. In the learning process the teacher is recommended to provide good quality teaching and learning activities, and to further refine these activities, a new media is needed in the learning process. Because based on the results of interviews with several teachers, it can be concluded that in the learning process students are less motivated, especially in the extra hours or evening hours and the lack of interaction makes students respond less and less. For this reason, in an effort to realize the quality of learning, new learning media are created that educate students such as educational games, where students can experience learning while playing. This can be used as a modern example, especially in the learning process of SMP Negeri 2 Purbalingga students. In accordance with the description above, this research takes the title